Nondestructive test methods for concrete bridges: A review - Rehman, Sardar Kashif Ur; Ibrahim, Zainah; Memon, Shazim Ali; Jameel, Mohammed (Construction and Building Materials, 2016)
NDT methods applicable to concrete bridges are reviewed. The methodology, advantages and disadvantages along with up to date research on NDT methods are presented. Different damage levels, having less dependence on inspector judgment, are suggested. Moreover, a flow chart based on damage level along with NDT methods and potential remedial measures are proposed for periodic health monitoring of structures.
Keywords: Concrete bridges; Damage levels; NDT methods; Remedial measures; Structural health monitoring; Research Subject Categories::TECHNOLOGY::Engineering physics